2017
DOI: 10.1371/journal.pone.0174333
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of diabetes mellitus on hepatocellular carcinoma: Special emphasis from the BCLC perspective

Abstract: BackgroundDiabetes mellitus (DM) is associated with higher incidence and poorer prognosis of hepatocellular carcinoma (HCC). The influence of DM on patient survival in different HCC stages is not known.MethodsA prospective dataset of 3,182 HCC patients was collected between 2002 and 2014. Patients were divided into three groups according to BCLC stages (BCLC stage 0 and stage A, BCLC stage B, BCLC stage C and stage D). We compared the cumulative survival rate of diabetic and non-diabetic patients in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Su et al investigated the effects of DM on survival in 3,182 HCC patients and used the BCLC staging criteria (25). They reported that diabetic patients had a poorer prognosis.…”
Section: Results:-mentioning
confidence: 99%
“…Su et al investigated the effects of DM on survival in 3,182 HCC patients and used the BCLC staging criteria (25). They reported that diabetic patients had a poorer prognosis.…”
Section: Results:-mentioning
confidence: 99%
“… 21 , 28 , 29 A recent study showed that diabetes was a predictor of decreased survival in the interferon era but not the direct-acting antiviral era, but the reasons for this are unclear. 30 Finally, it also appears that BCLC stage is important, as Su et al reported lower survival rates in HCC patients with diabetes and BCLC stage 0, A, and B, but no difference in survival seen in stages C and D. 31 , 32 …”
Section: Discussionmentioning
confidence: 97%
“…First assumption was, fatty infiltration in liver, often can be seen in diabetic patients, resulted in poor echogenicity and might have hindered HCC early detection; however, ultrasonographic fatty liver was not a predictor for HCC detection failure. On the other hand, diabetes mellitus is more prevalent in patients with advanced HCC compared to those with early HCC . Therefore, it seems highly probable that increased insulin resistance and hyperinsulinaemia in diabetes might upregulate the production of insulin‐like growth factor‐1 (IGF‐1), which stimulates cell proliferation, inhibits apoptosis and increase tissue turn over .…”
Section: Discussionmentioning
confidence: 99%
“…The biological , diabetes mellitus status. Cumulative incidence rates of HCC detection failure after 5 years of surveillance were higher in patients with clinical cirrhosis (liver cirrhosis vs nonliver cirrhosis; 3.1% vs 0.6%; P < 0.001), higher AFP levels (AFP ≥ 9 ng/mL vs AFP < 9 ng/mL; 8.7% vs 1.0%, P < 0.001), higher LS values (LS ≥ 11.7 kPa vs LS < 11.7 kPa; 5.7% vs 0.4%; P < 0.001), and diabetes mellitus (diabetes mellitus vs nondiabetes mellitus; 4.3% vs 0.6%; P < 0.001) 51,52 Therefore, it seems highly probable that increased insulin resistance and hyperinsulinaemia in diabetes might upregulate the production of insulin-like growth factor-1 (IGF-1), which stimulates cell proliferation, inhibits apoptosis and increase tissue turn over. 53,54 This leads to hepatocarcinogenesis and accelerated tumour growth.…”
Section: False Positive Lesions In Ultrasonographymentioning
confidence: 97%